Preparation method and application of nano-enzyme flexible sensor for monitoring gout

Through the functional modification of nanomaterials on the flexible pattern AU electrode, a high -sensitive uric acid and allex biosensor have been constructed to solve the problem of insufficient complexity and sensitivity to detect equipment in existing technologies, and realize the gout biological biology in the sweat. Real -time and high -sensitivity testing of logo.

CN119375321APending Publication Date: 2025-01-28NANJING UNIV OF POSTS & TELECOMM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411657297.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing methods for detecting uric acid and xanthine have problems with insufficient complexity, stability and sensitivity of sensing equipment, making it difficult to achieve high sensitivity and real-time monitoring.

Method used

The dual -channel flexible pattern AU electrode is used, and the nanomaterial is functionally modified to build a high -sensitive uric acid and illuminomy biosensor. The electrochemical signal is passed directly to the data processing system to achieve real -time monitoring.

Benefits of technology

A high -sensitive detection of changes in the concentration of uric acid and xanthine has the advantages of fast detection speed, high sensitivity, and wide detection range, and can monitor the changes in these gout biomarkers in sweat in real time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119375321A_ABST
    Figure CN119375321A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a nano-enzyme flexible sensor for monitoring gout, according to the scheme, based on a flexible polyethylene glycol terephthalate (PET) substrate material, a sensing electrode is prepared through evaporation patterning, and sensing electrode functionalization is achieved in combination with a precious metal nanoparticle electrodeposition technology; the high-sensitivity gout biomarker detection sensor is simply and easily constructed, changes of concentration of uric acid and xanthine in sweat can be monitored in real time, and timely medical monitoring service is provided for prevention of gout and hyperuricemia diseases and treatment of patients. A scanning electron microscope is used for electrode modification morphology characterization, and an electrochemical workstation is used for electrode sensing performance characterization. The sensor realizes the function of dynamically monitoring uric acid and xanthine in sweat, and has the characteristics of high detection speed, high sensitivity and wide detection range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention specifically relates to a method for preparing a flexible wearable sensor for real-time and highly sensitive detection of gout biomarker concentration changes in sweat, and belongs to the field of biological applications of nanomaterials. Background Art

[0002] Wearable sensors have broad prospects in the development of personalized medical devices due to their non-invasive detection, dynamic monitoring, and timely feedback. Sweat is a liquid produced by the sweat gland secretion system during physiological metabolism, containing glucose, lactic acid, uric acid, xanthine, cortisol, K + 、Na + The sweat monitoring system is a non-invasive wearable sweat sensor that can monitor the health of the human body. Compared with traditional blood monitoring, sweat monitoring can greatly reduce the possibility of human body invasion and is safer.

[0003] Excessive accumulation of uric acid and abnormal xanthine metabolism can lead to gout and hyperuricemia. Xanthine is metabolized by xanthine oxidase to form uric acid. Under healthy conditions, the concentration of uric acid in the blood is between 85 and 420 μM, and the level of xanthine in urine is about 40 to 160 μM. Uric acid and xanthine are redox active and can be directly detected electrochemically in sweat.

[0004] Metal nanomaterials have the characteristics of morphological and structural diversity, chemical stability, and biocompatibility, and are widely used in sensors, imaging, catalysis, information storage and other fields. Among various metal nanostructure synthesis technologies (such as electrodeposition, vapor deposition, hydrothermal synthesis, template synthesis, etc.), electrodeposition synthesis technology is to directly construct nanomaterials of different morphologies on the electrode surface through electrocatalytic oxidation-reduction methods. Electrodeposition technology can prepare nanostructures of different morphologies (such as spherical, branch-like, nano-island-like) by adjusting the proportion and concentration of the precursor solution and the conditions of electrodeposition (potential, current, time).

[0005] At present, there are many methods for detecting uric acid and xanthine, such as fluorescence, spectrophotometry, colorimetry, high performance liquid chromatography, etc. However, these methods are greatly limited in application due to problems such as the complexity of the sensor equipment, sensor stability, and sensor sensitivity.

[0006] By modifying the metal nanoparticle material on the surface of the electrochemical sensor electrode, the advantages of both can be fully utilized. The special morphology of the metal nanoparticles can be used to electrocatalyze the target. The electrochemical signal in the process can be directly transmitted to the data processing system through the electrode. The concentration of the target in the measured environmental liquid can be read based on the linear relationship obtained by a large number of preliminary experimental measurements. This sensor construction method is simple and easy to implement. It can monitor the changes in the concentration of uric acid and xanthine in sweat in real time, and provide timely medical monitoring services for the prevention of gout and hyperuricemia and the treatment of patients. Summary of the invention

[0007] In order to obtain highly sensitive uric acid and xanthine biosensors, the present invention is based on a dual-channel flexible patterned Au electrode, and its working area is functionalized with nanomaterials. The constructed sensor can detect uric acid and xanthine with high sensitivity. The sensor has the advantages of fast detection speed, high sensitivity, and wide detection range for gout biomarkers. A method for preparing a flexible wearable sensor for detecting changes in the concentration of gout biomarkers in sweat, the technical scheme is as follows:

[0008] 1) The patterned electrode is prepared in the following manner:

[0009] Double-channel Au patterned electrodes were prepared on flexible PET film using an evaporation deposition instrument.

[0010] 2) Functional modification of nanomaterials in the electrode working area is carried out in the following ways:

[0011] Step 1. Electrode activation

[0012] Polyacrylic acid (PAA) and polyethyleneimine (PEI) were used to activate the electrode surface. 6 μL of 20% PAA and 6 μL of 20% PEI were incubated on the electrode surface in sequence, each incubation time was 10 min, and the cycle was repeated 3 times to fully activate the electrode surface. After each activation incubation, the incubated area was rinsed with ultrapure water and dried with nitrogen. It was important to keep the airflow parallel to the plane where the electrode was located to avoid airflow damage to the flexible patterned electrode.

[0013] Step 2. Deposition modification

[0014] Use polydimethylsilane (PDMS) to prepare an elastic ring to enclose the deposition liquid. The inner diameter of the PDMS ring is 7mm, the height is 8mm, and the internal volume is 300μL~360μL. The PDMS ring is adhered around the working electrode, and a pipette is used to inject 300μL of a mixed solution of HAuCl4 and Na2PdCl4 deposition precursors prepared in a ratio of 1:1 (the ratio can be selected from 1:2 to 2:1). A three-electrode system is used, with a patterned circular electrode as the working electrode, a platinum wire as the counter electrode, and Ag / AgCl as the reference electrode. Using the chronoamperometric working mode of the electrochemical workstation, a potential of -0.3V~0.3V is applied to the electrode, the stimulation time interval is 0.1s, and the deposition time is 300s. After the deposition, the electrode is rinsed with ultrapure water and blown dry with nitrogen. When the voltage is 0.3, the nanostructure of gold-palladium electrodeposited on the surface of the prepared flexible electrode is shown in the attached figure. Figure 1 shown.

[0015] An application of a flexible wearable sensor for monitoring gout biomarkers in sweat, specifically the detection of uric acid and xanthine:

[0016] 300 μL of uric acid and xanthine solutions of different concentrations were dripped onto the prepared sensor electrode probes, and the oxidation current signal of the electrode for gout biomarkers was collected by the three-electrode system of the electrochemical workstation to obtain the differential pulse voltammetric current density change curve with the potential in the range of 0V to 0.8V and 0V to 1.1V. When the uric acid concentration changed from 0.5μM to 10mM, the peak position was in the range of 0.48V to 0.52V, and the peak current density increased from 15μA·cm -2 Change to 880μA·cm -2 As attached Figure 2 The relationship between the peak current density and uric acid concentration is shown in the attached figure. Figure 3 As shown in the figure, the two showed a linear relationship, the minimum detection limit reached 0.05μM, and the linear relationship was: y = 11.594Cua-173.41. When the xanthine concentration changed from 0.1μM to 0.8mM, the peak position was near 1.0V, and the peak value increased from 155μA·cm -2 Change to 255μA·cm -2 As attached Figure 4 The relationship between the peak current density and xanthine concentration is shown in the attached figure. Figure 5 As shown, the two showed a linear relationship, and the minimum detection limit reached 0.05 μM. The linear relationship when the xanthine concentration changed from 0.1 μM to 0.1 mM was: y = 0.402Cxa + 142.5, and the linear relationship when the xanthine concentration changed from 0.1 mM to 0.8 mM was: y = 0.08Cxa + 173.6.

[0017] Beneficial Effects

[0018] The electrocatalytic oxidation process of uric acid and xanthine by this sensor can be characterized by the three-electrode system of differential pulse voltammetry of the electrochemical workstation. The electrochemical signals collected in the test sweat environment are converted into the concentration results of uric acid and xanthine in the sweat environment through the linear relationship curve. This sensor has the characteristics of real-time data transmission, fast detection speed, high sensitivity and wide detection range. In the sweat environment, the sensor can display the oxidation process of uric acid in the potential range of 0V to 0.8V, and the oxidation process of xanthine in the potential range of 0V to 1.1V, and identify the corresponding uric acid and xanthine concentrations through the peak position current density value, so as to realize the concentration sensing of uric acid and xanthine in sweat. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Image of the nanostructure of gold-palladium electrodeposited on the surface of a flexible electrode.

[0020] Figure 2 It is a differential pulse voltammetry current density change curve of the gold-palladium nanoparticle modified electrode in the present invention under the conditions of different concentrations of uric acid.

[0021] Figure 3 It is a relationship curve between the peak current density value and the concentration in the presence of different concentrations of uric acid in the present invention.

[0022] Figure 4 The present invention is a differential pulse voltammetry current density variation curve of the gold-palladium nanoparticle modified electrode in the presence of xanthine at different concentrations.

[0023] Figure 5 It is a relationship curve between the peak current density value and the concentration in the presence of different concentrations of xanthine in the present invention. DETAILED DESCRIPTION

[0024] The present invention is further described in detail below in conjunction with embodiments, so that those skilled in the art can refer to the description to implement preparation and application.

[0025] It should be understood that the terms “comprising”, “including” and “having” used herein do not exclude the use or addition of one or more other device elements, and combinations thereof.

[0026] Example 1

[0027] The present embodiment provides a flexible wearable sensor for monitoring uric acid and xanthine in sweat, and the functional modification preparation method of the electrode nanoparticles is as follows: the mother liquor A is a chloroauric acid (HAuCl4) solution with a concentration of 200mM, the mother liquor B is a sodium chloropalladate (Na2PdCl4) or a similar noble metal solution with a concentration of 50mM, and the mother liquors are diluted and mixed in a ratio of 1:1. Before electrodeposition modification, the electrode is incubated for 10 minutes with 6μL of 20% polyacrylic acid (PAA) and 6μL of 20% polyethyleneimine (PEI). After each incubation, the electrode incubation area is rinsed with ultrapure water, then dried with nitrogen, and the operation is repeated three times. The chronoamperometry is used, with the modified electrode as the working electrode, the platinum wire as the counter electrode, and the Ag / AgCl as the reference electrode. The potential is set to -0.3V, the time interval is set to 0.1s, and the deposition time is set to 300s. 300 μL of a deposition precursor solution with a gold and palladium concentration of 5 mM was taken and electrodeposited in the working area of ​​the dual-channel Au electrode to form an alloy nano-island structure.

[0028] Example 2

[0029] Mother solution A is chloroauric acid (HAuCl4) solution with a concentration of 200mM, and mother solution B is sodium chloropalladate (Na2PdCl4) or a similar noble metal solution with a concentration of 50mM. The mother solutions are diluted and mixed in a ratio of 1:1. Before electrodeposition modification, the electrode is incubated for 10min surface activation with 6μL of 20% polyacrylic acid (PAA) and 6μL of 20% polyethyleneimine (PEI). After each incubation, the electrode incubation area is rinsed with ultrapure water, then blown dry with nitrogen, and the operation is repeated three times. The chronoamperometry method is used, with the modified electrode as the working electrode, platinum wire as the counter electrode, Ag / AgCl as the reference electrode, the potential is set to -0.1V, the time interval is set to 0.1s, and the deposition time is set to 300s. Take 300μL of the deposition precursor solution with a gold and palladium concentration of 5mM, and electrodeposit the alloy nano-island structure in the working area of ​​the dual-channel Au electrode.

[0030] Example 3

[0031] Mother solution A is chloroauric acid (HAuCl4) solution with a concentration of 200mM, and mother solution B is sodium chloropalladate (Na2PdCl4) or a similar noble metal solution with a concentration of 50mM. The mother solutions are diluted and mixed in a ratio of 1:1. Before electrodeposition modification, the electrode is incubated for 10min surface activation with 6μL of 20% polyacrylic acid (PAA) and 6μL of 20% polyethyleneimine (PEI). After each incubation, the electrode incubation area is rinsed with ultrapure water, then blown dry with nitrogen, and the operation is repeated three times. The chronoamperometry method is used, with the modified electrode as the working electrode, platinum wire as the counter electrode, Ag / AgCl as the reference electrode, the potential is set to 0.1V, the time interval is set to 0.1s, and the deposition time is set to 300s. Take 300μL of the deposition precursor solution with a gold and palladium concentration of 5mM, and electrodeposit the alloy nano-island structure in the working area of ​​the dual-channel Au electrode.

[0032] Example 4

[0033] Mother solution A is chloroauric acid (HAuCl4) solution with a concentration of 200mM, and mother solution B is sodium chloropalladate (Na2PdCl4) or a similar noble metal solution with a concentration of 50mM. The mother solutions are diluted and mixed in a ratio of 1:1. Before electrodeposition modification, the electrode is treated with 6μL of 20% polyacrylic acid (PAA) and 6μL of 20% polyethyleneimine (PEI) for 10 minutes of surface activation incubation. After each incubation, the electrode incubation area is rinsed with ultrapure water, then blown dry with nitrogen, and the operation is repeated three times. The chronoamperometry method is used, with the modified electrode as the working electrode, the platinum wire as the counter electrode, and Ag / AgCl as the reference electrode. The potential is set to 0.3V, the time interval is set to 0.1s, and the deposition time is set to 300s. Take 300μL of the deposition precursor solution with a gold and palladium concentration of 5mM, and electrodeposit it in the working area of ​​the dual-channel Au electrode to form an alloy nano-island structure, as shown in the attached Figure 1 shown.

[0034] Example 5

[0035] 300 μL of 100 μM uric acid solution was dripped onto the prepared sensor electrode probe, and the oxidation current signal of the electrode for gout biomarkers was collected by the three-electrode system of the electrochemical workstation to obtain the differential pulse voltammetric current density change curve with a potential range of 0V to 0.8V. The results showed that the peak position was at 0.48V, as shown in the attached figure. Figure 2 As shown. The peak current density is 2.9 μA·cm -2 , as attached Figure 3 shown.

Claims

1. A method for preparing a nanozyme flexible sensor for monitoring gout, characterized in that: The preparation steps are as follows: 1) patterning a dual-channel Au electrode on a flexible PET substrate by thermal evaporation; 2) using electrochemical deposition technology to precipitate the metal from the solution and deposit and modify the surface of the patterned electrode working area with a nanostructure.

2. The preparation method according to claim 1, characterized in that The specific steps of 2) are: 2-1) Prepare a solution with HAuCl4 chloroauric acid mother solution, Na2PdCl4 sodium chloropalladate or the same type of precious metal mother solution. Before electrodeposition modification, the electrode is surface activated and incubated with polyacrylic acid PAA and polyethyleneimine PEI; 2-2) Incubate the electrode with 4-6 μL of 20% PAA and 4-6 μL of 20% PEI in sequence. After each incubation, rinse the electrode incubation area with ultrapure water, then blow dry with nitrogen, repeat the operation, and use the chronoamperometry method, with the modified electrode as the working electrode, the platinum wire as the counter electrode, and the Ag / AgCl as the reference electrode. Select the potential in the range of -0.3 V to 0.3 V, set the time interval and deposition time; 2-3) Take a gold-palladium deposition precursor solution and electro-deposit it in the working area of ​​the dual-channel Au electrode to form an alloy nano-island structure, which is evenly distributed on the electrode surface. The nano-island particle size is in the range of 100 to 400 nm, and small spherical particles of 5 to 10 nm are attached to the surface of the island structure.

3. The preparation method according to claim 2, characterized in that: The concentrations of the chloroauric acid HAuCl4 mother liquor, sodium chloropalladate Na2PdCl4 or the same type of precious metal mother liquor in 2-1) are 200mM and 50mM respectively, and the ratio range of the matching solution is 1:2 to 2:

1.

4. The preparation method according to claim 2, characterized in that: The incubation time in 2-2) is 8 min to 12 min, and the operation is repeated three times, the time interval is set to 0.1 s, and the deposition time is set to 300 s to 360 s.

5. The preparation method according to claim 2, characterized in that: The above 2-3) deposition precursor solution with a gold-palladium concentration of 5 mM is 300 μL to 360 μL.

6. An application of a nanozyme flexible sensor for monitoring gout, characterized in that, for the detection of uric acid: uric acid solutions of different concentrations are dripped onto the sensor electrodes respectively, and the electrode current signal of differential pulse voltammetry within the acquisition range is collected to obtain the current density change curve of uric acid of different concentrations undergoing oxidation on the electrode surface, as well as the relationship curve between the peak current density and the uric acid concentration; the pulse voltammetry peak current density changes linearly with the concentration, and the higher the concentration, the greater the peak current density.

7. The use according to claim 6, characterized in that The amount of uric acid solution of different concentrations added was 300 μL, the range of electrode current signal collected by internal differential pulse voltammetry was 0V to 0.8V; the uric acid detection concentration was 0.1 μM to 12 mM.

8. An application of a nanozyme flexible sensor for monitoring gout, characterized in that: Detection of xanthine: xanthine solutions of different concentrations were added to the sensor electrodes, and the electrode current signal of differential pulse voltammetry was collected; the peak current density of pulse voltammetry changed linearly with the concentration, and the higher the concentration, the greater the peak current density.

9. The method of application according to claim 8, characterized in that The concentrations of the xanthine solutions added dropwise are 300 μL of different concentrations, the electrode current signal range of the differential pulse voltammetry is 0V to 1.1V, and the xanthine detection concentration is 0.05 μM to 0.9 mM.

10. The use according to claim 6 or 8, characterized in that The minimum detection limit of the sensor is 0.01 μM.